Investigations on the Wear Performance of Coated Tools in Machining UNS S32101 Duplex Stainless Steel - Sousa, Vitor F. C. (2022)
Due to their high mechanical property values and corrosion resistance, duplex stainless steels (DSSs) are used for a wide variety of industrial applications. DSSs are also selected for applications that require, especially, high corrosion resistance and overall good mechanical properties, such as in the naval and oil-gas exploration industries. The obtention of components made from these materials is quite problematic, as DSSs are considered difficult-to-machine alloys. In this work, the developed wear during milling of the UNS S32101 DSS alloy is presented, employing four types of milling tools with different geometries and coatings. The influence of feed rate and cutting length variations on the tools’ wear and their performance was evaluated. The used tools had two and four flutes with different coatings: TiAlN, TiAlSiN and AlCrN. The cutting behavior of these tools was analyzed by collecting data regarding the cutting forces developed during machining and evaluating the machined surface quality for each tool. After testing, the tools were submitted to SEM analysis, enabling the identification of the wear mechanisms and quantification of flank wear, as well as identifying the early stages of the development of these mechanisms. A comparison of all the tested tools was made, determining that the TiAlSiN-coated tools produced highly satisfactory results, especially in terms of sustained flank wear.